Promoting the cyclic and rate performance of lithium-rich ternary materials via surface modification and lattice expansion. Issue 113 (30th October 2015) - Mezaal, Mohammed Adnan; Qu, Limin; Li, Guanghua; Zhang, Rui; Xuejiao, Jiang; Zhang, Ke; Liu, Wei; Lei, Lixu
Abstract : Nickel-rich layered lithium transition-metal oxides have been studied intensively as high-energy positive-electrode materials for lithium batteries because of their high specific capacity and relatively low-cost. Abstract : Nickel-rich layered lithium transition-metal oxides, Li1.2 Ni1− x M x O2 (M = transition metal), have been studied intensively as high-energy positive-electrode materials for lithium batteries because of their high specific capacity and relatively low-cost. However, oxygen loss from the lattice during the initial charge and gradual structural transformation during cycling can lead to capacity degradation and potential decay of the cathode materials. This is due to the small size and highly oxidizing nature of tetravalent nickel. Herein, we report for the first time a series of promising core–shell structured positive-electrode materials with a general formula [Li1.2− x Na x Ni0.62 Co0.14 Mn0.248 O2 ], where x = 0, 0.05, 0.08, 0.10 and 0.12. The results clearly show that the manganese oxide coating has greatly improved the cycling stability and inhibited side reactions with the electrolytes. However, the manganese oxide coating can also retard the electrode reactions because it extends the diffusion path for lithium ion and results in increases in the charge transfer resistance. Sodium doping expands the lattice due to the fact that Na has higher ionic radii than those of Li. This facilitates the diffusion of Li-ions, reduces the charge transfer resistance and improves the electrochemical performance of the materials. Furthermore, sodium doping not only improves the discharge capacity, but it also improves the cycling stability even further. This is because Na has higher ionic radii than that of Li and hence Na has less tendency to migrate to "tetrahedral" sites in the Li/Na layer and restrict the structural transformation. However, the addition of Na higher than 0.1 decreases the capacity as Na has a higher weight than that of Li.